KETIMPANGAN PEMBANGUNAN WILAYAH DI PROVINSI KALIMANTAN TENGAH (KAJIAN PADA KABUPATEN KOTAWARINGIN TIMUR DAN PEMEKARANNYA) - Luthfian Riza Sanjaya; Endriatmo Soetarto; Andrea Emma Pravitasari (Diponegoro University, 2019)
Inequality of regional development is a common problem faced by all provinces in Indonesia, not least the Province of Central Kalimantan. Regional inequality stems from factors that should be minimized. The aims of this research were 1)to tanalyze the trend of regional development inequality in Central Kalimantan Province and the factors that influence it 2) to analyze the hierarchy of regional development in Kotawaringin Timur (Kotim) Regency and developing area 3) to analyze regional development inequality and influenced factors using Geographical Weighted Regression (GWR).4) to prepare regional directives and policy development plans. The method used are Williamson's Index, Multiple Regression with Unbalanced Panel, weighted Skalogram, and GWR. The results of this study indicated that the level of inequality in Central Kalimantan Province tends to decrease with RHGU as the most dominant factor. The regional development of the area at the sub-district level showed spatial patterns which indicated an imbalance between the northern and southern regions. The GWR resulted also shows that RHGU is still the dominant factor with the same influence throughout the research area. Thus, the urgency of agrarian reform in plantation areas is important to be implemented immediately.